2008
DOI: 10.1038/sj.bjc.6604740
|View full text |Cite|
|
Sign up to set email alerts
|

Human thyroid tumours, the puzzling lessons from E7 and RET/PTC3 transgenic mice

Abstract: Human rearranged RET/PTC3 (papillary thyroid carcinoma) proto-oncogene and high-risk human papillomavirus (HPV) type 16 E7 oncogene induces in the mouse a neoplastic transformation of thyroid follicular cells. We present a detailed immuno-histological study (170 mouse thyroids: RET/PTC3, E7, wild type, 2-to 10-month-old) with cell cycle proliferation and signalling pathway indicators. The characteristics of both models are different. There is an 'oncogene dependent' cellular signature, maintained at all studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…RET/PTC3-transgenic mice develop PTC with lymph node metastases (21). A careful and detailed histological comparison of RET/PTC3-and human papillomavirus type 16 E7-transgenic (Tg-E7) mice showed that RET/PTC3 mice appear as a partial and transient model of human PTCs, while human papillomavirus type 16 E7-transgenic mice present with a dominant goitrous pattern of thyroid changes (22). In younger Mct8…”
Section: Discussionmentioning
confidence: 99%
“…RET/PTC3-transgenic mice develop PTC with lymph node metastases (21). A careful and detailed histological comparison of RET/PTC3-and human papillomavirus type 16 E7-transgenic (Tg-E7) mice showed that RET/PTC3 mice appear as a partial and transient model of human PTCs, while human papillomavirus type 16 E7-transgenic mice present with a dominant goitrous pattern of thyroid changes (22). In younger Mct8…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the fact that expression of one oncogene (eg RET-PTC3) in the thyroid of mice elicits thyroid growth and dedifferentiation but not general carcinomas. In fact the thyroids of such mice get, gene expression wise, more and more different from human papillary carcinomas as they age (Burniat et al, 2008). However they develop different localized, then extensive lesions… obviously as the result of further localized oncogenic event.…”
Section: Thyroid Signal Transduction Oncogenes and Protooncogenesmentioning
confidence: 99%
“…Moreover the use of inducible tissue-specific knock-down or oncogene expression systems should allow a clearer dissection of carcinogenic pathways in vivo. However, transgenic mice expressing an oncogene in the thyroid (eg RET/PTC3) develop tumors whose morphology, gene expression and evolution are partly different from their human counterpart (Burniat et al, 2008;Jin et al, 2008).…”
Section: Page 5 Of 62mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, microarray gene profiling was used to assess the similarity in the altered gene expression patterns between PTC in humans and RET/PTC3 mice [67,68]. Several human PTC characteristics were observed in RET/PTC3 mice: overexpression of many immune-related genes, regulation of human PTC markers, upregulation of EGF-like growth factors and significant regulation of angiogenesis, and extracellular matrix remodeling-related genes [67, 68].…”
Section: Mouse Models Of Thyroid Cancermentioning
confidence: 99%